1997
DOI: 10.1051/jp4:1997222
|View full text |Cite
|
Sign up to set email alerts
|

Stripe structure and Non-Homogeneity of the CuO2Plane by Joint EXAFS and Diffraction

Abstract: Local structure of the Cu02 plane in Bi2Sr2CaCu208+8 (Bi2212) superconductor has been solved by joint Cu K-edge extended X-ray absorption fine structure (EXAFS) and anomalous X-ray diffraction. The Cu-0 pair distribution function (PDF) has been measured by EXAFS and diffraction. The displacement of the Cu ions along the c-axis shows largest amplitude and anharmonic character. The results show flat stripes of the Cu02 lattice of width L = 15 =& 0.5 A that are separated by stripes of bent Cu02 plane.The modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…It has also been called a Feshbach shape resonance [23][24][25]. The high superconducting critical temperature in cuprates [28][29][30][31][32][33] and diborides [33][34][35] has been assigned to these resonances.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been called a Feshbach shape resonance [23][24][25]. The high superconducting critical temperature in cuprates [28][29][30][31][32][33] and diborides [33][34][35] has been assigned to these resonances.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown theoretically that the presence of holes makes layered antiferromagnets unstable against phase separation into holerich and hole-poor regions at intermediate length scales [1][2][3][4][5][6]. At the same time, there is growing experimental evidence for mesoscopic striped phases and their effect on the electronic properties in perovskite materials [7][8][9][10][11][12][13][14][15][16]. It is therefore of crucial interest to obtain direct experimental information on the charge distribution within the superconducting CuO 2 planes of high-T c cuprates.…”
Section: Introductionmentioning
confidence: 99%
“…(i) Our model emphasizes the ordered charge arrangement in a unit cell. The width of charge tapes W ≈ a/2 (a is the in-plane lattice parameter) is by order of magnitude less than the width of stripes which is about 15 Å [20,22,[27][28][29]. In terms of our model any attempt to extend stripe width up to a few lattice constants would result in strong contradiction with the observed behaviour of the CEF parameters.…”
Section: Discussionmentioning
confidence: 56%
“…It has been theoretically shown that dilute holes in a layered antiferromagnet can be unstable against phase separation into hole-rich and hole-poor regions at intermediate length scales [2][3][4][5][6][7]. At the same time there is growing experimental evidence for mesoscopic striped phases and their effect on the electronic properties in perovskite materials [20][21][22][23][24][25][26][27][28][29]. It is therefore of crucial interest to obtain direct experimental information on charge distribution within the superconducting CuO 2 planes of high-T c cuprates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation